Floristic Composition Of Forest Formation At Mahua, Crocker Range National Park, Sabah - Isa, Ipor; Hamsawi, Sani; Tawan, C.S (ARBEC Publishing, 2002)
The floristic composition of mixed dipterocarp forest of Mahua Crocker Range National Park Sabah was investigated with respect to plant diversity, vegetative structure and physiognomy. The assessment of above ground biomass, relative frequency, relative density, relative dominance and important values of tree species revealed that Duabanga moluccana tops the list of the tree species studied with respect to dominance. This was followed by Knema ashtonii, Agathis lanceolata, Lithocarpus cantleyanus and Litsea ochracea. The least dominant species was Xanthophyllum schizocarpum and followed by Baringtonia sarcostachys, Shorea maxwelliana, Alseodaphne insignis, Litsea resinosa, Beilsmedia pauciflora, Alseodaphne foxiana, Endiandra kingiana and Litsea machilifolia.